Prevalence and factors associated to back pain in adults from the northeast of São Paulo, Brazil: a population-based study - Vitta, Alberto De; Conti, Marta Helena Souza De; Maciel, Nicoly Machado; Trize, Débora De Melo; Corrente, José Eduardo; Ruiz, Tânia (Pontifícia Universidade Católica do Paraná, 2017)
AbstractIntroduction: Back pain has become a serious public health problem.Objective: To determine the prevalence of back pain in a population-based sample of subjects over 20 years old living in the city of Bauru (São Paulo, Brazil) and to analyze the associations to variables- sociodemographic, ergonomic and lifestyle-related - and to morbidity.Methods: a cross-sectional study which evaluated 600 adults over 20 years old, both gender and living in the city. We used a structured protocol and the Nordic questionnaire. Also, we developed a descriptive analysis, bivariate and multivariate by binary logistic regression.Results: The prevalence of back pain was of 50.3% (CI 46.3 to 54.3), since 42.3% (CI 36.9 to 48.0) in men and 57.6% (CI 51.9 to 63.0) in women, with statistical significant difference (p = 0.001). Different variables remained in final models when assessed by gender. For male to be widowed and divorced and smoking habits and, for women to be widowed and divorced, to work in seated position and to perform occupational activities that demand carrying and lifting weight.Conclusion: We verified high prevalence in back pain in the population of Bauru and high association to widowed/divorced in both gender, with women performing occupational activities usually or always in seated position, those who carry or lift weight in work and men who smoke.

ResumoIntrodução: As dores na coluna vertebral tornaram-se um grave problema de saúde pública.Objetivo: Verificar a prevalência de dor na coluna vertebral em uma amostra de base populacional de indivíduos com idade superior a 20 anos residentes na cidade de Bauru (São Paulo, Brasil) e analisar as associações as variáveis sociodemográficas, ergonômicas, relacionadas ao estilo de vida e a morbidade referida.Métodos: Estudo transversal que avaliou 600 adultos com idade superior a 20 anos, de ambos os sexos, moradores da zona urbana do município. Utilizou-se um protocolo estruturado e o questionário Nórdico. Realizou-se uma análise descritiva, bivariada e multivariada por regressão logística binária.Resultados: A prevalência de dor nas costas foi 50,3% (IC95% 46,3 a 54,3), sendo que, 42,3% (IC95% 36,9 a 48,0) nos homens e 57,6% (IC95% 51,9 a 63,0) nas mulheres com diferença estatisticamente significativa (p = 0,001). Diferentes variáveis permaneceram nos modelos finais ao se considerarem, em separado, o sexo masculino e o feminino. Ser viúvo e separado e tabagismo para o sexo masculino e, para o feminino, ser viúva e separada, trabalho na postura sentada e exercer atividades ocupacionais que exigem transporte e carregamento de peso.Conclusão: Verificou uma prevalência alta de dor na coluna vertebral na população de Bauru e marcante associação com marcante associação com os viúvos/separados, em ambos os sexos, com as mulheres que exercem suas atividades ocupacionais, geralmente ou sempre, na postura sentada, naqueles que transportam e carregam pesos regulamente no trabalho e nos homens tabagistas.
Prevalência e fatores associados à dor na coluna vertebral em adultos do noroeste de São Paulo, Brasil: estudo de base populacional
Keywords: Epidemiology; Spine; Back Pain; Neck Pain; Risk Factors; Epidemiologia; Coluna Vertebral; Dor Lombar; Dor Cervical; Fatores de Risco